2019
DOI: 10.1021/acs.iecr.9b01546
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Deactivation of Cu/ZnO/Al2O3 Catalyst for CO2 Hydrogenation to Methanol

Abstract: The catalytic performance of Cu/ZnO/Al 2 O 3 (CuZnAl) catalyst for CO 2 hydrogenation to methanol was investigated over a period of 720 h time-on-stream, which showed that the space time yield of CH 3 OH was decreased by 34.5% during the long-term testing. Different characterization techniques, including X-ray diffraction (XRD), scanning electron microscopy, high resolution transmission electron microscopy, X-ray photoelectron spectroscopy (XPS), and N 2 O adsorption experiments, were applied to study the deac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
161
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(166 citation statements)
references
References 51 publications
5
161
0
Order By: Relevance
“…In both cases of CO and CO 2 hydrogenation, CZA-H catalyst exhibited lower coke deposition than CZA-L. According to the TGA analysis and catalytic activity results, it was suggested that the CZA-L catalyst with high ZnO content can migrate and generate the graphitic coke to block the active sites (Liang et al, 2019;Laudenschleger et al, 2020;Okemoto et al, 2020). Furthermore, large amounts of carbon deposition over CZA catalysts were formed by the decomposition of CO and CO 2 molecules with the reduction of ZnO and CuO, and Cu oxidation (Chiang et al, 2018), which was related to low catalytic activity as shown in Figure 6.…”
Section: The Deactivation Of Spent Catalystsmentioning
confidence: 99%
“…In both cases of CO and CO 2 hydrogenation, CZA-H catalyst exhibited lower coke deposition than CZA-L. According to the TGA analysis and catalytic activity results, it was suggested that the CZA-L catalyst with high ZnO content can migrate and generate the graphitic coke to block the active sites (Liang et al, 2019;Laudenschleger et al, 2020;Okemoto et al, 2020). Furthermore, large amounts of carbon deposition over CZA catalysts were formed by the decomposition of CO and CO 2 molecules with the reduction of ZnO and CuO, and Cu oxidation (Chiang et al, 2018), which was related to low catalytic activity as shown in Figure 6.…”
Section: The Deactivation Of Spent Catalystsmentioning
confidence: 99%
“…The water generated in the RWGS during CO 2 reduction to methanol deactivates the catalyst, causing speciation of Cu active phase and phase separation (Kung, 1992;Liang et al, 2019;Prasňikar et al, 2019). Sahibzada et al observed a lower rate of methanol production in the presence of water in the H 2 /CO 2 feed (Sahibzada et al, 1998).…”
Section: Deactivation Of Methanol Synthesis Catalystsmentioning
confidence: 99%
“…When using a zeolite catalyst, C2+ hydrocarbons of a certain composition were obtained by hydrogenation of carbon dioxide with the use of zeolite and mixed zeolite-oxide systems as catalysts. The dependence of the activity of these catalysts in the hydrogenation of CO2 to methanol and hydrocarbons on the amount of acid sites was studied [94][95][96]. The C5-C11 gasoline fraction was obtained with high selectivity on the In2O3 / HZSM-5 catalyst.…”
Section: Hydrogenation Of Carbon Dioxide To C2+ Hydrocarbonsmentioning
confidence: 99%